Effectiveness of cognitive–behavioural therapies of varying complexity in reducing depression in adults: systematic review and network meta-analysis. (August 2022) - Angelakis, Ioannis; Huggett, Charlotte; Gooding, Patricia; Panagioti, Maria; Hodkinson, Alexander
Abstract : Background: Cognitive–behavioural therapy (CBT) is frequently used as an umbrella term to include a variety of psychological interventions. It remains unclear whether more complex CBT contributes to greater depression reduction. Aims: To (a) compare the effectiveness of core, complex and ultra-complex CBT against other psychological intervention, medication, treatment-as-usual and no treatment in reducing depression at post-treatment and in the long term and (b) explore important factors that could moderate the effectiveness of these interventions. Method: MEDLINE, PsycInfo, Embase, Web of Science and the Cochrane Register of Controlled Trials were searched to November 2021. Only randomised controlled trials were eligible for the subsequent network meta-analysis. Results: We included 107 studies based on 15 248 participants. Core (s.m.d. = −1.14, 95% credible interval (CrI) −1.72 to −0.55 [m.d. = −8.44]), complex (s.m.d. = −1.24, 95% CrI −1.85 to −0.64 [m.d. = −9.18]) and ultra-complex CBT (s.m.d. = −1.45, 95% CrI −1.88 to −1.02 [m.d. = −10.73]) were all significant in reducing depression up to 6 months from treatment onset. The significant benefits of the ultra-complex (s.m.d. = −1.09, 95% CrI −1.61 to −0.56 [m.d. = −8.07]) and complex CBT (s.m.d. = −0.73, 95% CrI −1.36 to −0.11 [m.d. = −5.40]) extended beyond 6 months. Ultra-complex CBT was most effective in individuals presenting comorbid mental health problems and when delivered by non-mental health specialists. Ultra-complex and complex CBT were more effective for people younger than 59 years. Conclusions: For people without comorbid conditions healthcare and policy organisations should invest in core CBT. For people <59 years of age with comorbid conditions investments should focus on ultra-complex and complex CBT delivered without the help of mental health professionals.